The Role of Alternative Energy Sources in European Countries - Karimova Salima Elamonovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This article explores the importance of alternative energy sources in European countries, their impact on economic growth, environmental protection, and sustainable development. It highlights the progress achieved in renewable energy technologies, as well as the challenges faced during the transition to clean energy systems.